O Ministério Público como ator de efetivação e fomento de políticas públicas para a defesa do direito fundamental à moradia das pessoas em situação de rua - Marcarini, Lélio (2022)
Housing is one of the most complex issues related to social rights. The crisis generated by the shortage of housing and the financialization of access to this fundamental right stress and expose one of the greatest violations of human rights, leading people who, without alternatives, find a place to live on the streets. This group of excluded, made invisible and marginalized people almost lost the prospect of survival; bitter the challenges of life in the city and tends to increase in scale due to the pandemic crisis caused by covid-19 and unemployment. This research analyzes whether the public housing policy of the municipalities that make up the Pole X of Social Assistance, in the northwest region of Espírito Santo, includes the necessary resources to guarantee this fundamental right to homeless people, as well as whether the Ministry's performance Audiences in public hearings can be an alternative for the municipal executive branch to have projects and activities that guarantee the right to housing for homeless people. Using a dialectical matrix methodological approach, the research aims to analyze the importance of developing intersectoral and regional actions aimed at homeless people; verify whether the performance of the Public Prosecutor's Office in the public hearings of the participatory budget in the municipalities effectively contributes to the inclusion in the municipal planning laws of programs and activities aimed at meeting the housing policy for homeless people; analyze investments in housing based on the financial statements of the municipalities that are part of the Polo Regional X published on the transparency portals; and verify compliance with the Sustainable Development Goals (SDG – Agenda 2030) in such municipalities. In this scenario, proposals capable of promoting the emancipation of this vulnerable social group that inhabits cities, providing them with access to adequate housing, assume particular relevance, especially if the Housing First concept is considered, which is structured inversely to the policy in stages. The main results show that the municipalities that integrate Polo Regional X do not invest in subsidized housing policies especially aimed at homeless people; that these municipalities lack adherence to the SDGs set out in the 2030 Agenda; that the protection networks do not have temporary shelters or social rent to support the assistance and social approaches carried out by the respective municipal secretariats of Social Assistance; and that there is low popular participation in public hearings. Therefore, the Public Prosecutor's Office, as an institution that induces public policies and an agent of social transformation, has a prominent role in the implementation and realization of the fundamental right to housing, especially in the participation and direct intervention with other actors and entities of civil society